2007
DOI: 10.4049/jimmunol.179.7.4357
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 Signaling Renders Quiescent Naive and Memory CD4+ T Cells More Susceptible to Productive Infection with X4 and R5 HIV-Type 1

Abstract: It has been recently demonstrated that circulating microbial products are responsible for a systemic immune activation in individuals infected with HIV-type 1. Bacterial products carry structural conserved motifs recognized by TLRs. Some TLR members are expressed in primary human CD4+ T cells but the precise functional role played by these pattern recognition receptors is still imprecise. In this study, we report that engagement of TLR2 in quiescent naive and memory CD4+ T cells leads to the acquisition of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
50
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 85 publications
5
50
1
Order By: Relevance
“…ϩ T cells independently of TCR sensitization has been observed (45). A similar effect on neonatal naive CD8 ϩ T cells was observed during the course of our study (data not shown).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…ϩ T cells independently of TCR sensitization has been observed (45). A similar effect on neonatal naive CD8 ϩ T cells was observed during the course of our study (data not shown).…”
Section: Discussionsupporting
confidence: 71%
“…The direct action of TLR9-triggered murine CD4 ϩ T cells in enhancing humoral immunity by causing increased Ig titers has also been described (42). An indirect association with human disease has also been posited through the demonstration of alterations in the expression of various TLRs on T cell subsets between healthy and ill humans during filarial (43), hepatitis C (44), and HIV (45) infections.…”
Section: Discussionmentioning
confidence: 99%
“…Although HIV-1 was observed in intracellular vesicles, cell-bound HIV-1 was primarily transmitted after Pam3CSK4 stimulation. Pam3CSK4 might upregulate the expression of receptors that increase HIV-1 capture, such as heparan sulfate proteoglycans (46) (47). However, we observed increased trans-infection, which is independent of fusion of HIV-1 with LCs, strongly suggesting that increased HIV-1 capture but not infection is responsible for transmission after Pam3CSK4 stimulation.…”
Section: Discussioncontrasting
confidence: 55%
“…Second, STIs cause inflammation that leads to the recruitment of immune cells to the site of inflammation, thereby increasing the size of the HIV-1 target cell population (88,128,136). Third, STIs promote a favorable local environment for HIV-1 replication both by directly activating HIV-1 target cells and by inducing the release of cytokines that favor virus replication through the engagement of Toll-like receptors (TLRs) and other innate immune sensors in cells present in the mucosa (9,10,37,57,75,122,134,145,146,161).…”
mentioning
confidence: 99%